Nursing as a profession: reflections on the conceptions of incoming academics about work and its precariousness. - Andrade, L. M. S.; Caetano, E.; Maier, S. R. O. (Scientific Electronic Archives, 2018)
Nursing since its inception carries design help, donations and vocation with its meaning, but this way of thinking idealized contrasts with the difficulties of effective worker nurse, who sells his labor power and is subject to the capitalist mode of exploitation thus ensuring their livelihoods. At any moment in history, the work takes different forms depending on the modes of production, and only human beings are able to create and recreate it. The aim of this paper was to analyze the conceptions that undergraduate nursing students have about the profession at the beginning of the course and relate these concepts to the precariousness of work in nursing. We used the field research methodology, with a qualitative approach, we conducted semi-structured interviews with incoming students in the undergraduate nursing course at a Federal Higher Education Institution (HEI), and the sample had a total of 9 interviewees, which were Analyzed through Content Analysis, and used historical dialectical materialism as a reference for discussion, since through a historical and social interpretation of reality we proceed to correlate these conceptions. Thus, the following results emerged: "care as nursing object of work" and "'improvisation or precarization of work in nursing?". As results it was possible to verify how the vocational and aid conception may be related to the difficulty of the workers in fighting for working conditions and the close perceived relation of the capitalist mode of production to the forms of precariousness of work in health . New studies should indicate the need to deepen the theme and thus make it possible to overcome the characteristic limits of this profession. Â 